Penciptaan Setan untuk Kebaikan Manusia - Muktafi Muktafi (Islamica: Jurnal Studi Keislaman, 2012)
In Arabic Satan means an enemy, one who is distant, misled, burnt, disowned from the grace of God and displaced from His mercy. He is so distant that he cannot any longer hear and know the truth. He is so arrogant that he became the victim of his own attitude. In the Qur?an the word Satan is always mentioned in its concrete from (ma?rifah) which means that the existence and threat of the Satan is true and real. This also means that Satan is created solely to mischief man on his earthly life and mislead him from the grace of God. Different views however have been expressed to the extent that the creation of the Satan may also be understood as an indication of God?s mercy upon His creation especially human being. If it is not because of Satan, human being would not be able to distinguish between good and vice. And it is exactly because of Satan that human being ?upon his success to avoid his deceive- may be raised to the higher status as human being. This paper is concerned with this controversy and with the logical implication that emerges thereof. It is ultimately about tracing the Qur?anic and prophetic notion of what Satan is, and what it means to be human.